Alteration in morphological features of Puntius javanicus liver exposed to copper sulfate - Sabullah M.K.; Ahmad S.A.; Shukor M.Y.; Gansau A.J.; Shamaan N.A.; Khalid A.; Sulaiman M.R. (Universiti Putra Malaysia, 2024)
Indexed by SCOPUS/ERA